PENGARUH SIZE, GROWTH OF ASSETS, PROFITABILITY DAN ASSETS STRUCTURE TERHADAP CAPITAL STRUCTURE (Studi Kasus Pada Perusahaan Manufaktur Go Public Di Bursa Efek Indonesia) (Students' Journal of Economic and Management, 2013)
This study aims to examine and describe the influence of firm size (size), asset growth (growth of assets), profitability (profitability) and the structure of assets (asset structure) of the capital structure (capital structure) to the manufacturing company went public on stock exchanges Indonesia. Research technique used was purposive sampling method. Mechanical testing data used in this study include classical and Assumption Testing Normality and Regression Analysis. The analysis and discussion of this study indicate that the variable size and assets structure proved to be positively and significantly to the capital structure variable, the variable growth of assets not proven to have positive and significant impact on capital structure variables and variable profitability and significant negative effect on capital structure variables. simultaneously the size, growth of assets, profitability and assets structure significantly influence the capital structure. Keywords: Size, Growth Of Assets, Profitability, Assets  Structure and Capital Structure